Social Culture And Economic Development In The Batak Angkola Community In Padang Lawas Utara - Siregar, Enni Sari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
Economic development is an effort to reduce poverty in order to achieve prosperity through increased income. Economic development can be influenced by economic, social and environmental factors. This study aims to identify the socio-cultural relationship with economic development through a literature study with the object of the Batak Angkola community in North Padang Lawas district. The results of the study indicate that in theory the socio-cultural environment has a relationship with economic development. The socio-cultural environment includes traditional ceremonies such as birth customs, marriage customs and death customs. In addition, poverty, human resources and capital formation are also related to the success of economic development. This local wisdom is still ongoing today because the Batak Angkola people adhere to the philosophy of Hamoraon, Hasangapon, Hagabeon